Integrated municipal solid waste planning and management ( IMSWPM ) in developing countries : A Conceptual Framework - Yudoko, Gatot (Jurnal Manajemen Teknologi, 2004)
Problems of municipal solid waste planning and management (MSWPM) in developing countries are multiple and interrelated. The nature of these problems has three major implications. First, the conventional approach with its focus on collection, transportation, and disposal activities and its primary goal of technical efficiency in service provision in no longer appreciate. Second, involvement and participation from various actors other than the local waste authorities is called for. Partnership of stakeholdes in MSWPM are necessary. Third, the increasingly complex issues associated with MSWPM and the inability of the conventional approach to deal with them lead to the necessity of an integrated approach to MSWPM in developing countries. This paper is the first of two parts. In this part, a conceptual of an integrated solid waste planning and management (IMSWPM) for developing countries is formulated. Any integrated approach to resources and environmental planning and management embodies two basic dimensions: substantive and procedural. The former can be characterized by four main attributes: holistic, inter-connective, goal oriented, and strategic. Thus, the proposed framework suggests that integrated municipal solid waste planning and management is holistic when it takes into account various perspectives, such as public and environmental health, physical, technical, social/cultural, economical/financial, institutional and managerial, political, and legal; inter-connective as it is based on interactions among four main components: activities, actor (stakeholders), option, and aspects (perspectives); goal oriented through the identification of common goals among stakeholders; and strategic when it identifies key issues associated with taste generation, source separation,service provision, composting, sorting and recycling, and safe disposal.Â Keywords:Â municipal solid waste management, development, conceptual framework